The next challenge for WOrld wide Robotized Tele-Echography eXperiment (WORTEX 2012): From engineering success to healthcare delivery - Vieyres, Pierre; Novales, Cyril; Rivas, R.; Vilcahuaman, Luis; Sandoval, Juan; Clark, T.; DeStigter, K.; Josserand, L.; Morrison, Zoe; Robertson, Ann; Avgousti, Sotiris; Morette, Nicolas; et al. (My University, 2013)
Access to good quality healthcare remains difficult for many patients whether they live in developed or developing countries. In developed countries, specialist medical expertise is concentrated in major hospitals in urban settings both to improve clinical outcomes and as a strategy to reduce the costs of specialist healthcare delivery. In developing countries, millions of people have limited, if any, routine access to a healthcare system and due to economic and cultural factors the accessibility of any services may be restricted. In both cases, geographical, socio-political, cultural and economic factors produce ‘medically isolated areas’ where patients find themselves disadvantaged in terms of timely diagnosis and expert and/or expensive treatment. The robotized teleechography approach, also referred to as robotized teleultrasound, offers a potential solution to diagnostic imaging in medically isolated areas. It is designed for patients requiring ultrasound scans for routine care (e.g., ante natal care) and for diagnostic imaging to investigate acute and medical emergencies conditions, including trauma care and responses to natural disasters such as earthquakes. The robotized teleechography system can hold any standard ultrasound probe; this lightweight system is positioned on the patient’s body by a healthcare assistant. The medical expert, a clinician with expertise in ultrasound imaging and diagnosis, is in a distant location and, using a dedicated joystick, remotely controls the scanning via any available communication link (Internet, satellite). The WORTEX2012 intercontinental trials of the system conducted last year successfully demonstrated the feasibility of remote robotized tele-echography in a range of cultural, technical and clinical contexts. In addition to the engineering success, these trials provided positive feedback from the participating clinicians and patients on using the system and on the system’s perceived potential to transform healthcare in medically isolated areas. The next challenge is to show evidence that this innovative technology can deliver on its promise if introduced into routine healthcare.